Skill development in marine fisheries: Some reflections on the issues and way outs - SAJESH, V K; SURESH, A; MOHANTY, A K; SINGH, VIKRAM; RAVISHANKAR, C N (The Indian Journal of Animal Sciences, 2021)
Indian fisheries sector is receiving increasing attention and policy support owing to the livelihood and foreign exchange potential of the sector apart from its nutritional significance. The Government of India has initiated ‘Blue Revolution’ to augment the fish production and to strengthen the fish based value chain. But, unequipped manpower is often highlighted as one of the major deterrents for leveraging the full potential in harvest and post-harvest fisheries sector, which is highly skill intensive in nature. The issue would emerge more serious in case of marine fisheries. In this paper, we attempted to deliberate on the issue of skill-deficit that would emerge in harvest and post-harvest sectors of marine fisheries sector in India, and suggest measures to address them.